2013
DOI: 10.1194/jlr.d033399
|View full text |Cite
|
Sign up to set email alerts
|

In vivo hepatic lipid quantification using MRS at 7 Tesla in a mouse model of glycogen storage disease type 1a

Abstract: This article is available online at http://www.jlr.org Glycogen storage disease type 1 (GSD 1) is an autosomal recessive metabolic disorder resulting in severe impairment of glucose production and large accumulation of lipids within hepatocytes (steatosis) ( 1, 2 ). The phenotype of GSD 1 results from a defect in the glucose-6 phosphatase (G6Pase) complex, leading to severe hypoglycemia due to the loss of endogenous glucose production. Despite a strict diet, patients with GSD 1 develop hepatomegaly and steatos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
25
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(32 citation statements)
references
References 46 publications
5
25
2
Order By: Relevance
“…Therefore, corrections for signal losses due to T 2 and J ‐coupling were dispensed as further corroborated by the phantom experiments (Table ). The T 2 values of the fatty‐acyl protons in the soybean oil‐in‐water emulsion (12–19 ms) were comparable to those observed in the mouse liver in vivo and shorter than those reported for pure oils , which is relevant for validation of the method, and further supports the accuracy of our results in the mouse liver in vivo . Moreover, changes in the saturation degree of the fatty‐acyl chains could be successfully identified by 1 H‐MRS in mixtures prepared from SO (high levels of PUFA) and PO (high levels of MUFA), demonstrating the applicability of the method to follow alterations of the hepatic fatty acid composition in vivo .…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Therefore, corrections for signal losses due to T 2 and J ‐coupling were dispensed as further corroborated by the phantom experiments (Table ). The T 2 values of the fatty‐acyl protons in the soybean oil‐in‐water emulsion (12–19 ms) were comparable to those observed in the mouse liver in vivo and shorter than those reported for pure oils , which is relevant for validation of the method, and further supports the accuracy of our results in the mouse liver in vivo . Moreover, changes in the saturation degree of the fatty‐acyl chains could be successfully identified by 1 H‐MRS in mixtures prepared from SO (high levels of PUFA) and PO (high levels of MUFA), demonstrating the applicability of the method to follow alterations of the hepatic fatty acid composition in vivo .…”
Section: Discussionsupporting
confidence: 88%
“…Nonetheless, in a study where spectra were acquired with STEAM from the liver of healthy volunteers , accounting for J ‐coupling modulation yielded T 2 values comparable to those obtained from the simplified monoexponential model, supporting the accuracy of our T 2 estimations. Hepatic water T 2 was 8 ms, shorter than that reported for mice at 11.7 , 9.4 and 7 T . T 2 shortening with increasing magnetic field strength has been previously observed for brain metabolites .…”
Section: Discussionmentioning
confidence: 42%
See 1 more Smart Citation
“…However, insulin similarly induced Akt phosphorylation in the SWAT of L-G6pc Suppression of HGP increases the oleate/palmitate ratio in the liver We previously demonstrated that the specific inactivation of glucose 6-phosphatase in the liver leads to steatosis [8,22], due to the transcriptional activation of ChREBP [7]. The suppression of HGP in lean mice also led to an increase in hepatic glucose 6-phosphate content (Fig.…”
Section: Resultsmentioning
confidence: 74%
“…Liver 1 H‐MRS showed that PSS mice had higher levels of hepatic lipids than their age‐matched controls, but still below the range of 10–30% reported for mouse models of hepatic steatosis . Fatty degeneration of the liver has been described in humans, as well as in cats and dogs, with PSS.…”
Section: Discussionmentioning
confidence: 93%